Delmar's basic care nursing skills CD-ROM - Altman, Gaylene Bouska; Buchsel, Patricia; Coxon, Valerie; Delmar Thomson Learning (Albany : Delmar Thomson Learning, 2000)
Covers over 50 basic nursing skills, is a full-color interactive product following the five-step nursing process. It is developed in clear, concise, easy-to-follow format to help promote competence in fundamental nursing skills. Some of the skills covered include mobility, hygiene, basic assessment, heat/cold, urinary catheter, specimens, orthopedic, and many least invasive procedures
System requirements: 100 MHz Pentium w/24 MB of RAM; Windows 95 or newer; CD-ROM drive (8x or faster); sound card and speakers; SVGA 24-bit color display; 8 MB of free disk space
Keywords: Nursing; Nursing Care